'XX'–Sacroplasty: A Novel Technique for Management of "H-Type" Sacral Insufficiency Fractures. (28th September 2022) - Lotan, Raphael; Hershkovich, Oded; Bronstein, Yigal; Finkelstein, Joel
Objective: Examine the feasibility, safety, and results of a novel sacral percutaneous injection technique ("XX") addressing both the vertical and horizontal aspects of sacral insufficiency fractures (SIF). Methods: Prospective cohort study. Eight consecutive SIF patients with immobility and pain investigated using CT and nuclear imaging confirmed "H"-type fracture. Demographics, pain level, and ambulation status were recorded. The long-term quality of life was evaluated using the ODI questionnaire and pain VAS scores. Sacroplasty procedures in prone positioning using fluoroscopy were used to insert 2 bone trochars through the S1 pedicles and 2 trochars through the sacral ale aiming toward the SIJ, thus forming 2 "X" trochar formations. Balloon kyphoplasty was done through the trocars, and PMM was injected. Postoperative ambulation and VAS were recorded. Results: Average age was 81.5 years (±3.4 years). The time from presenting symptoms to hospital admission was 2 days to 4 months. All patients were significantly limited with ambulation. None had a neurologic compromise. Sacroplasty was performed with 2 cases that required additional lumbar kyphoplasty. The mean operative time was 54 min (±14). The average exposure was 19 mGy (±12 mGy). Two patients had cement leaks. CT and X-rays revealed good cement filling of the fractures sacral alae and body of S1. The average postoperative hospitalization was 10 days. All patients reported postoperatively pain relief immediately and were able to walk better. Follow-up time was 17 ± 12 months. Follow-up VAS was 2.7 (±2) and ODI was 57.3% (±21%). Conclusion: "XX" technique showed good outcomes for patients with higher complexity SIF, using the same principles as for lumbar VPL/KPL, and was found to be safe and effective.